Degree and Timing of Intensive Blood Pressure Lowering on Hematoma Growth in Intracerebral Hemorrhage: Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial-2 Results. Issue 6 (June 2016) - Carcel, Cheryl; Wang, Xia; Sato, Shoichiro; Stapf, Christian; Sandset, Else Charlotte; Delcourt, Candice; Arima, Hisatomi; Robinson, Thompson; Lavados, Pablo; Chalmers, John; Anderson, Craig S.
Abstract : Background and Purpose—: Degree and timing of blood pressure (BP) lowering treatment in relation to hematoma growth were investigated in the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial-2 (INTERACT2). Methods—: INTERACT2 was an international clinical trial of intensive (target systolic BP [SBP], <140 mm Hg) versus guideline-recommended (SBP, <180 mm Hg) BP lowering in 2839 patients within 6 hours of spontaneous intracerebral hemorrhage and elevated SBP (150–220 mm Hg), in which 964 had repeat cranial computed tomography at 24 hours. ANCOVA models assessed categories of SBP reduction and time to target SBP on 24-hour hematoma growth. Results—: Greater SBP reduction was associated with reduced hematoma growth (13.3, 5.0, and 3.0 mL for <10, 10–20, and ≥20 mm Hg, respectively; P trend<0.001). In the intensive treatment group (n=491), the least mean hematoma growth was in patients who achieved target SBP <1 hour (2.6 mL) versus to those in target at 1 to 6 (4.7 mL) and >6 hours (5.4 mL). The smallest mean absolute hematoma growth (2.0 mL) was in those achieving target SBP 5 to 8 times versus 3 to 4 (3.1 mL) and 0 to 2 times (5.2 mL). Conclusions—: Intensive BP lowering with greater SBP reduction, which is achieved quickly and maintained consistently, seems to provide protection against hematoma growth for 24 hours. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00716079. Abstract : Supplemental Digital Content is available in the text.